The activation states of LFA-1 (alphaL beta2) and related integrins - Cheng, Ming (2008)
Leukocyte integrins (beta2 integrins) are involved in many immune and inflammatory responses. The key function of leukocytes is impaired in the LAD-I patients due to the defects in beta2 gene. Two missense LAD-1 mutations N329S and R571C were studied. alphaLbeta2N329S can mediate constitutive adhesion to both ICAM-1 and ICAM-3, alphaIIbbeta3N339S which is corresponding to N329S in beta2 also can mediate adhesion to fibrinogen in the absence of activation reagents. Through mutagenesis analysis and conformation study, we demonstrate that this Asn is critical in shaping the I-like domain by stabilizing the conformation of the a7 helix and the ?6-a7 loop in the I-like domain.